Engelhardtia In Pleistocene of Kashmir - Puri, G. S. (Indian Forester, 1946)
The paper describes a fossil leaflet of Engelhardtis colebrookeana, which was collected by tbe author from the Karewa deposits of Kashmir at Laredura, in the Pir Panjal Range.A comparison of the past and present distribution of this species shows that the valley at one time during the Pleistocene was occupied by rain forests.A detailed past and present distribution of the genus ,Is given and it has been pointed out that whereas the genus with numerous species was best represented in Southern Europe during the Miocene times it witnessed a decline during the Pliocene and by the Pleistocene Period it had become extinct from this region where it is unrepresented at the present time. On the other hand, as many as 15 distinct species of the genus are represented in the modern flora of south-eastern Asia from where a single fossil species has been discovered from the above evidence it is concluded that the genus was more widely spread during the past than it is to-day.